A comparison of regional anesthesia techniques in patients undergoing video-assisted thoracic surgery: A network meta-analysis. (September 2022) - Sandeep, Bhushan; Huang, Xin; Li, Yuan; Xiong, Dan; Zhu, Bo; Xiao, Zongwei
Abstract: Background: Postoperative pain control remains challenging in patients undergoing video-assisted thoracoscopic surgery (VATS). This study aimed to investigate the relative efficacy of different regional anesthesia interventions for VATS using a Network Meta analysis (NMA). Methods: A literature search was conducted for NMA using Pubmed, The Cochrane Library, Embase, and the Web of Science databases to identify all randomized controlled trials (RCTs) that compared the analgesic effects of different regional analgesia techniques from inception to February 2022. The primary outcome was opioid consumption during the first 24 h postoperatively. The secondary outcomes were morphine consumption at 48 h postoperatively, pain intensity, postoperative nausea and vomiting, and hospital length of stay. Pain scores at two different intervals from different regional analgesia techniques were measured and investigated in this NMA. Results: A total of 38 RCTs (2224 patients) were included. Two studies compared three arm interventions of intercostal nerve block (ICNB) vs. thoracic paravertebral block (TPVB) vs. erector spinae plane block (ESPB) in intravenous morphine consumption at 24 h and 48 h postoperatively, and showed patients who received TPVB had less demand for morphine than ICNB and ESPB (P = 0.001, P = 0.001). For resting pain scores at 24 h postoperatively, ESPB was superior to serratus anterior plane block (SAPB) (P = 0.01), and TPVB provided effective analgesia compared to ICNB, retrolaminar block (RLB), and ESPB (P = 0.05, P = 0.01, P = 0.03). Similarly, pain scores at rest at 48 h, SAPB and TPVB showed the best results (P = 0.04, P = 0.001, P = 0.01) compared with local infiltration analgesia (LIA), ICNB, RLB, and ESPB. Additionally, pain scores at coughing at 24 h and 48 h, TPVB showed superior results compared with RLB, ESPB(P = 0.02, P = 0.02, P = 0.03). SAPB was superior to LIA in reducing the incidence of postoperative nausea and vomiting (P = 0.04). Conclusion: In regional anaesthesia, TPVB is a better option than other analgesic methods, and its combination with other methods can be beneficial. However, our findings can only provide objective evidence. Clinicians should choose the treatment course based on the individual patient's condition and clinical situation. Highlights: There is no established analgesia method for postoperative analgesia for VATS. TPVB is a better option than other analgesic methods for VATS patients. Recently, SAPB and ESPB in VAST seems clinically safe and easier to perform. Network Meta Analysis can make indirect quantitative comparisons.